Are total thyroidectomy and loboisthmectomy effective and safe in benign thyroid diseases? An analysis of 420 patients - Demirhan, Hasan; Hamit, Bahtiyar; Sünter, Ahmet Volkan; Yiğit, Özgür (The European Research Journal, 2018)
Objective. Ideal thyroid surgery is still a debated issue due to preoperative pathology and varying rates of postoperative incidental carcinoma and complications. In our clinic loboisthmectomy and bilateral total thyroidectomy are the treatment of choice in benign nodular thyroid diseases. The objective of this study was to analyse effectiveness and safety of bilateral total thyroidectomy and loboisthmectomy for treating benign thyroid diseases. Methods. Patient charts of the subjects that have undergone thyroid surgery due to benign thyroid diseases between 2009-2015 were evaluated retrospectively. We extracted data including number of patients, type of surgery, preoperative and postoperative pathologies and postoperative complications from departments medical records. Results. Four hundred and twenty patients including 98 (23.3%) male and 322 (76.7%) females aged between 14-80 years (mean; 47.3 ± 12.5) were included into the study. Bilateral total thyroidectomy was performed in 348 (82.9%) patients and loboisthmectomy was performed in 72 (17.1%). Mean duration of follow-up was 41 (range: 15-70) months. Incidental thyroid carcinoma rate was 24.5% (n = 103) in postoperative pathological examination. Temporary and permanent hypocalcemia was seen in 53 (15.2%) patients and 8 (2.3%), respectively. Permanent and transient recurrent laryngeal nerve palsy rate were 2.6% and 2.1%, respectively. Postoperative hematoma was observed in 7 (1.7%) patients. Conclusions. Incidental thyroid carcinoma is frequent in patients who had surgical operation for benign thyroid diseases. When revision surgeries and additional complications due to revision surgery in the remaining cases are kept in mind, bilateral total thyroidectomy or loboisthmectomy at the minimum can be considered as the ideal surgical approach for benign thyroid diseases.